Implementasi Metode Metode ROC dan Electre dalam Pemilihan Penerima Bantuan Sosial - Bangun, Budianto (Buletin Ilmiah Informatika Teknologi, 2024)
Determining social assistance recipients is one of the complex problems faced by the government in order to improve people's welfare. One method that can be used to solve this problem is to use a multicriteria decision-making method. In this research, two multicriteria decision-making methods, namely the ELECTRE (Elimination and Choice Expressing Reality) and ROC (Rank Order Centroid) methods, are implemented to assist in the process of selecting social assistance recipients. The ELECTRE method is used to perform pairwise comparisons between alternatives based on predetermined criteria. By using this method, unqualified alternatives will be eliminated, so that only the best alternative will be selected. Meanwhile, the ROC method is used to determine the weight of the criteria based on the ratings given by the decision maker. With this method, the ranking of each criterion is converted into a proportional weight, so that it can be used in the alternative evaluation process. From the results of the above calculations using the electre and roc methods, the alternative with the highest total score value is obtained, namely A7 Hasanudin Hasibuan